Screening a library of antibacterial compounds leads to discovery of novel inhibitors for Neisseria gonorrhoeae and Chlamydia trachomatis - Abdelsattar, Abdallah S.; Abutaleb, Nader S.; Seleem, Mohamed N. (PLOS ONE, 2026)
Chlamydia trachomatis and Neisseria gonorrhoeae were the most common bacteria causing sexually transmitted infections (STIs) in 2020, with 211 million cases worldwide. Despite the fact that the co-infections of N. gonorrhoeae with C. trachomatis are common, there is no single treatment effective against both pathogens. Ceftriaxone, the current recommended drug for gonococcal infections, is not effective against C. trachomatis. Additionally, N. gonorrhoeae has developed resistance against the drugs recommended for treating chlamydial infections. Therefore, new drugs capable of treating C. trachomatis/N. gonorrhoeae co-infections are needed. Drug repurposing is an attractive, fast-track approach for antimicrobial drug discovery. In an attempt to address the unmet need for development of C. trachomatis/N. gonorrhoeae therapeutics utilizing the drug repurposing approach, we screened the antibacterial compounds library against N. gonorrhoeae. This library encompasses a unique collection of 1,128 bioactive compounds with validated antibacterial activities. A total of 172 active hits were identified, and then repeated drugs with different salts or previously reported drugs were excluded before determining the minimum inhibitory concentrations (MICs) against N. gonorrhoeae FA1090. Thereafter, the anti-C. trachomatis activities of the 14 selected drugs were assessed. We identified gloxazone and SPR719 as promising agents with potent activities against both C. trachomatis and N. gonorrhoeae (MICs ≤ 1 µM). Collectively, SPR719 and gloxazone could be considered promising agents warranting further investigation to address the unmet need in the treatment of bacterial STIs.